ASYMMETRIC EFFECTS OF LOSS AND GAIN OF A FLORAL TRAIT ON POLLINATOR PREFERENCE. (8th July 2013) - Dell'Olivo, Alexandre; Kuhlemeier, Cris
<x xml:space="preserve">Abstract</x> Shifts in pollination syndromes involve coordinated changes in multiple floral traits. This raises the question of how plants can cope with rapid changes in pollinator availability by the slow process of accumulation of mutations in multiple genes. Here we study the transition from bee to hawkmoth pollination in the genus Petunia. Interspecific crosses followed by single locus introgressions were used to recreate putative intermediate evolutionary stages in the evolution of moth pollination. The effect of the loss/gain of petal color was asymmetric: it had no influence on the established pollinator but enhanced visitation by the new pollinator. Therefore, shifts in pollination syndromes may proceed through intermediate stages of reduced specialization and consequently enhanced reproductive assurance. The loss of petal color in moth‐pollinated Petunia involves null mutations in a single regulatory gene, An2. Such simple genetic changes may be sufficiently rapid and frequent to ensure survival during pollinator failure.